Psychological Well-Being, Marital Satisfaction, and Parental Burnout in Iranian Parents: The Effect of Home Quarantine During COVID-19 Outbreaks - Mousavi, Seyyedeh Fatemeh (Frontiers in Psychology, 2020)
Coronavirus as an infectious disease is now prevalent in many countries around the world which have recently led many governments to impose home quarantine and penalties for violating quarantine. Concerns and stress caused by social isolation led to personal and interactive reactions in some families, which are also culturally important to address. The stressful events need to change in lifestyle and people no longer simply feel satisfied after the changes. Changes caused by these events that led to stress and act as a threat to marital satisfaction and intimate relationships. Unexpected crises affect not only the couple's relationship but also the quality of the parent and the parental outcomes, as well as challenging the parents' ability and energy to perform the full responsibilities of parenting. This study was administrated with the aim of studying the psychological well-being and effect of home quarantine on marital satisfaction and parental exhaustion from parenting responsibilities during the prevalence of coronavirus in Iranian parents. A total of 213 parents of which 140 mothers (age:37.34±7.22; the marriage length 14.46±8.14) and 73 fathers (age: 41.95±8.6; the marriage length 15.64±10.07) voluntarily participated in the online survey in the period of February to April 2020 (a month after the prevalence of coronavirus in Iran) and completed World Health Organization's Psychological Well-being Index (WHO-5), the Kansas Marital Satisfaction Scale (KMSS), and Parental Burnout Assessment (BPA) in the two sections before and after the prevalence of COVID-19 with past and present verbs. The results of repeated measurement tests showed that the effect of home quarantine on marital satisfaction and parental burnout was not significant in both groups of fathers and mothers (p > .01). Also, the interactive effect of the home quarantine and gender were not significant on marital satisfaction and parental burnout (p > .01). The results showed that mothers were significantly reported higher parental burnout than the fathers, but the fathers had higher scores in marital satisfaction and psychological well-being (p <.01). Supportive resources in family-based culture may play an essential role in reducing the negative effects of the crisis in family interactions caused by the spread of COVID-19.